Fenomena LGBT Beserta Dampaknya di Indonesia - Regina Solihatul Afiyah (Gunung Djati Conference Series, 2023)
Indonesia is a country with a majority of followers of Islam. Along with the development of technology, many western cultures are gradually being implemented by Indonesian people. One of these western cultures is the normalization of LGBT. It has been seen that many teenagers in Indonesia openly admit that they like the same sex on social media. In this study, the authors aim to examine the LGBT phenomenon in Indonesia and its impact. The method used in this research is a qualitative method which is a literature study that uses books and other literature as the main object. The results of this study are that there are several negative impacts from the development of LGBT for Indonesian society, especially for adolescents. From this research we can conclude that LGBT behavior can have an impact on perpetrators and victims. The first impact will affect health, social impact, education impact and security impact.